Development of a telescope detector for Sr-90 detection - Hussain, Junaid (2022)
Nuclear catastrophes and accidents release harmful fission products containing long-lived (Se-79, Zr-93, Tc-99, Pd-107, Sn-126, I-129, and Cs-135) radioisotopes having half-life of hundreds of thousands or millions of years and short-lived (Kr-85, Sr-90, Ru-106, Cs-134, Cs-137, Pm-147, Sm-151, and Eu-155). After a few years, Cs-137 and Sr-90 radioisotopes with a half-life of around 30 years dominate. These dominating radioisotopes are potentially harmful for living creatures. They affect DNA, brain tissues, and even stick with bones. To study the possible radiation damages, one needs to prepare a sample which is an expensive, tedious, and long-awaited process.